Near Synonymy Analysis of Three Adverbials: Surprisingly, Astonishingly and Amazingly - İşler, Cemre (My University, 2022)
The purpose of this study is to investigate the extent of the similarities and differences among one-word adverbials (surprisingly, astonishingly, amazingly) in terms of meaning, register and collocational constraints. These adverbials are considered roughly synonymous of one another. But we should be skeptical about their full synonymy, though their dictionary meanings show that these words can be substitutable with one another. In order to demonstrate the extent of the similarities in terms of their meanings, three standard dictionaries of English were used. As for the extent of the differences in terms of their meanings, two dictionaries of synonymy discriminations were used. Also, the Corpus of Contemporary American English (COCA) was analyzed to provide further understanding to the differences among these words in terms of meaning, register and collocational constraints. According to the findings, though these words were given as interchangeable in meaning and considered synonyms of one another, they were actually not completely substitutable with one another. Rather, they differ in their shades of meanings. That is why these three words should be considered as near-synonyms. Also, the findings revealed that these three words differed from one another in terms of frequency of occurrences and the frequency of use across registers to a great extent. Finally, the findings showed that these three words mostly collocate with enough as post-modifier. However, only surprisingly collocate with not as pre-modifier.
Keywords: Near synonymy; adverbial; surprisingly; astonishingly; amazingly; COCA